EVALUASI KONDISI FISIK TUNASUSILA TERMINAL RIMBO BUJANG UNIT 2 KABUPATEN TEBO PROVINSI JAMBI - Putra, Muhamar Kodafi (Dharmas Education Journal (DE_Journal), 2023)
Most of the women who live in the area around Terminal Rimbo Bujang Unit 2 work as prostitutes who work from 18.00-03.00, of course they need good physical condition as well. If someone wants to do an activity with extraordinary intensity then he must be able to maintain and shape his physical condition very well, if the activity is done very well then there is a reserve ready to transfer energy so that someone can carry out activities that ooze sweat from night to dawn which is an activity or work done every day. The aim of the researchers is none other than to find out the physical condition of the prostitutes at the localization of the Rimbo Bujang Unit 2 Terminal which is experiencing its viability process. And this research is called "Qualitative Research". The results of this study reveal an evaluation of the physical condition of the prostitutes at the Rimbo Bujang Unit 2 Terminal where the activities of women who work as prostitutes there at night start their work with Zumba Gymnastics Activities (In the Morning), Jogging (In the Afternoon), and carrying out activities such as lifting weights that they make to resemble tools at the Gym as well as Drinking Jamu. Physically, the Prosecutors of the Rimbo Bujang Unit 2 Terminal have a work intensity that is very different on average from people who work in general, due to their work serving the lust of other men who are not their husbands and working in very cold night-dawn temperature conditions. The work they do aims to support their children because their status is widowed, caring for their parents.